Porovnání chromatografických metod pro stanovení ergosterolu a jejich využití při analýze půdy podhorské pastviny - Jirout, Jiří; Tříska, Jan; Růžičková, Kamila; Vrchotová, Naděžda; Šimek, Miloslav; Elhottová, Dana (Chemické listy, 2010)
Ergosterol, a biomarker of living saprotrophic fungi, was obtained from soil by microwave-assisted extraction and determined by GC-MS-MS, HPLC, and GC-FID. The GC-MS-MS technique was used to monitor fungal biomass in the soils differently impacted by overwintering cattle. The amount of ergosterol in soil increased from 0.93 ± 0.34 to 29.28 ± 3.07 ?g g?1 of soil. The detection limits in GC-MS-MS and HPLC methods were ca. ten times lower than in GC-FID. Whereas GC-MS-MS is the best method for monitoring the complex sterol profile in the environment, the selective MS-MS mode allowed the determination of ergosterol in complex matrices by elimination of coeluting peaks. The enrichment of cattleimpacted soils in non-fungal sterols (campesterol, stigmaserol and ß-sitosterol) and stanols (ergostanol, sitostanol) was due to digested plant materials and rumen microflora, suggesting significant biochemical changes in the pasture soils under study.
Keywords: půda; Financing, Organized; půdní mikrobiologie; Ergosterol; Soil Microbiology; financování organizované; Soil; ergosterol